2018
DOI: 10.3892/etm.2018.6848
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture stimulates the proliferation and differentiation of endogenous neural stem cells in a rat model of ischemic stroke

Abstract: Electroacupuncture (EA) may stimulate neurogenesis in animal models of ischemic stroke; however, the associated mechanisms are not clear. The present study aimed to evaluate the neurogenesis efficacy of EA on ischemic stroke and the underlying associated mechanisms. A model of middle cerebral artery occlusion (MCAO) was employed as the rat model of brain ischemia and reperfusion. EA treatment at the GV20 (Baihui) and GV14 (Dazhui) acupoints was conducted for 30 min daily following MCAO. Immunofluorescence was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…EA directly upregulated the gene expression of plasticity-related gene 5 (PRG5), which is a critical neurogenesis factor, and also upregulated the protein expression of postsynaptic density 95 (PSD95) and synaptophysin (SYP). Moreover, EA downregulated the expression of neurogenesis inhibitory molecules, including NogoA, lysophosphatidic acid, and RhoA, to improve the proliferation and differentiation of endogenous neural stem cells and synaptic plasticity in stroke rats ( Tan et al, 2018 ; Yang et al, 2022 ). Deng et al (2021) have reported that EA promoted differentiation of transplanted MSCs into neuron-like cells and expressions of BDNF and NGF proteins displaying therapeutic efficacy in ICH rats.…”
Section: Mechanisms Of Mesenchymal Stem Cells In Intracerebral Hemorr...mentioning
confidence: 99%
“…EA directly upregulated the gene expression of plasticity-related gene 5 (PRG5), which is a critical neurogenesis factor, and also upregulated the protein expression of postsynaptic density 95 (PSD95) and synaptophysin (SYP). Moreover, EA downregulated the expression of neurogenesis inhibitory molecules, including NogoA, lysophosphatidic acid, and RhoA, to improve the proliferation and differentiation of endogenous neural stem cells and synaptic plasticity in stroke rats ( Tan et al, 2018 ; Yang et al, 2022 ). Deng et al (2021) have reported that EA promoted differentiation of transplanted MSCs into neuron-like cells and expressions of BDNF and NGF proteins displaying therapeutic efficacy in ICH rats.…”
Section: Mechanisms Of Mesenchymal Stem Cells In Intracerebral Hemorr...mentioning
confidence: 99%
“…Thomas Broggini suggested that plppr5 , as an upstream molecule of ROCK, can overcome LPA and Nogo-A-induced neurite contraction caused by RhoA-ROCK-PIP5K kinase pathway activation ( 16 ). Recently, Tan et al found that electroacupuncture stimulation may be involved in the neuroprotective effect of cerebral ischemia-reperfusion rats mediated through plppr5/NogoA-LPA/RhoA signaling ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Nissl bodies (blue) staining in neural cells were clearly visible and distinct. Cells with Nissl staining in the cytoplasm and prominent nucleoli were identified as surviving neurones, whilst cells with shrunken shape, cavitation around the nucleus or loss of Nissl substance were considered damaged ( 43 ). Only whole neurones with visible nuclei were counted.…”
Section: Methodsmentioning
confidence: 99%